Amino acids, betaines and related ammonium compounds in Neapolitan limmo, a Mediterranean sweet lime, also known as lemoncetta Locrese. (24th August 2020) - Cautela, Domenico; De Sio, Francesco; Balestrieri, Maria Luisa; Casale, Rosario; Laratta, Bruna; Castaldo, Domenico; Pastore, Annalisa; Servillo, Luigi; DʼOnofrio, Nunzia
Abstract: BACKGROUND: The so‐called 'Neapolitan limmo' or 'lemoncetta Locrese' is an old and now rare Mediterranean sweet lime, similar to lemon but smaller. It is a fruit distinguished from orange, lemon, mandarin, and lime for its sweeter, watery, and non‐acidic taste, with a pH between 5.6 and 5.9. No compositional studies are currently available for this citrus fruit. Here we report, for the first time, the distribution in the limmo juice of free amino acids and their main derivatives such as betaines and related ammonium compounds. RESULTS: Seven proteinogenic amino acids (proline, asparagine, serine, aspartic acid, glutamine, alanine, and threonine) and a non‐protein amino acid ( γ ‐aminobutyric acid) characterize Neapolitan limmo juice. Proline betaine is the predominant betaine. The data were compared with those of other important citrus juices. CONCLUSION: The specific 'taste quality' of Neapolitan limmo juice can be attributed to its peculiar composition in amino acids. The species‐specific presence of the ammonium compound derivatives of the amino acid proline, with proline betaine as the predominant betaine, characterize the non‐acidic varieties of Mediterranean sweet lime. Our study constitutes an important step towards the repopulation of this ancient plant and its exploitation in food industry. © 2020 Society of Chemical Industry